The effects of chlorhexidine and ethanol on push-out bond strength of fiber posts - Victorino, Keli; Kuga, Milton; Duarte, Marco; Cavenago, Bruno; Só, Marcus; Pereira, Jefferson (Wolters Kluwer, 2016)
Context: Irrigation of root canals with chlorhexidine (CHX) and ethanol is common practice to prevent root canal infection during postplacement. However, pretreatment with these solvents may interfere with the bond strength of posts. Aims: This study aimed to evaluate if root dentin pretreatment using CHX and/or ethanol influences the push-out bond strength of fiber-reinforced composite resin (FRCR) posts. Materials and Methods: Fifty space posts prepared in endodontically treated extracted human canine roots were randomly divided into five groups (n = 10) according to the dentin pretreatment: Distilled water (W); 1% CHX diacetate solution (1C); CHX diacetate + 99% ethanol (1CE); 99% ethanol (E); and 2% CHX digluconate solution (2C). After pretreatment, the adhesive system (Peak Universal Bond; Ultradent, South Jordan, UT, USA) was applied in the root dentin and the FRCR was cemented with resin cement. Then, horizontal slices of 2 mm were obtained from each root third and the push-out bond strength was assessed. Statistical analysis was done using analysis of variance (ANOVA) and Tukey′s tests (P = 0.05). Results: At all thirds, 1CE and E groups presented similar push-out bond strength values (P > 0.05), which were higher than the other groups (P < 0.05). W, 1C, and 2C groups were similar (P > 0.05). Conclusion: The root dentin pretreatment with ethanol, alone or mixed with CHX diacetate increased the bond strength of FRCR luted with resin cement.
Keywords: Chlorhexidine (CHX); ethanol; fiber post; resin cements